Pocket elimination after osseous resective surgery: A systematic review and meta‐analysis. (20th March 2020) - Ferrarotti, Francesco; Giraudi, Marta; Citterio, Filippo; Fratini, Adriano; Gualini, Giacomo; Piccoli, Gian Marco; Mariani, Giulia Maria; Romano, Federica; Aimetti, Mario
Abstract: Aim: To systemically review the available evidence on the clinical performance of osseous resective surgery (ORS) in the treatment of residual periodontal defects in terms of pocket elimination and biological costs in patients with chronic periodontitis. Materials and methods: Three databases (PubMed, EMBASE and Cochrane) were searched up to January 2019. Clinical trials with a follow‐up duration of at least 12 months after ORS with or without fibre retention technique were included. Quantitative synthesis was conducted with random‐effect meta‐analysis. Results: Overall, 1, 765 studies were retrieved, of which 53 full‐text articles were screened by two reviewers. Finally, a total of three RCTs were included in the meta‐analysis. Random‐effect meta‐analysis showed a weighted mean percentage of pocket elimination (final PD ≤ 4 mm) at 12 months of 98.3% (95% CI: 96.8; 99.7) with I 2 of 26%. The weighted mean amount of resected bone was 0.87 mm (95% CI: 0.49; 1.25), and the weighted mean increase in gingival recession was 2.13 mm (95% CI: 1.49; 2.78) at 12 months. Conclusions: ORS represents an effective surgical approach for the elimination of residual periodontal pockets in the short to medium term. Additional randomized controlled clinical trials with data on pocket elimination are warranted.